2016
DOI: 10.1159/000445639
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Four Radiotracers in PET/CT on Diagnostic Accuracy for Prostate Cancer: A Bivariate Random-Effects Meta-Analysis

Abstract: Background/Aims: To date, several positron emission tomography/computed tomography (PET/CT) radiotracers including fluorine-18 fluorodeoxyglucose (18F-FDG), carbon-11 labeled choline (11C-choline), 18-F fluorocholine (18F-FCH) and carbon-11 acetate (11C-acetate) have already been assessed in the application of prostate cancer (PCa) diagnosis to some extent, the diagnostic efficiency of these radiotracers still remain controversial. As a result of this, we carried out this meta-analysis for the purpose of compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…Moreover, in 18 F-FDG PET/CT studies, the tracer showed overlapping uptake in normal, benign and malignant tissues resulting in poor specificity (18-20). A recent systematic review and meta-analysis of 3,586 men with PCa compared the diagnostic accuracy among four PET/CT radiotracers ( 18 F-FDG, 11 C-choline, 18 F-choline and 11 C-acetate) suggesting diagnostic superiority of 18 F-choline, ranked as the most favorable with the highest value of AUC (AUC =0.94; 95% CI: 0.92–0.96), whereas 18 F-FDG was the least favorable (AUC =0.73; 95% CI: 0.69–0.77) for PCa detection (2). On the other hand, a recent review suggests that, 18 F-FDG might be helpful for restaging purposes in patients with advanced PCa metastatic disease.…”
Section: F-fluorodeoxyglucose (18f-fdg)mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, in 18 F-FDG PET/CT studies, the tracer showed overlapping uptake in normal, benign and malignant tissues resulting in poor specificity (18-20). A recent systematic review and meta-analysis of 3,586 men with PCa compared the diagnostic accuracy among four PET/CT radiotracers ( 18 F-FDG, 11 C-choline, 18 F-choline and 11 C-acetate) suggesting diagnostic superiority of 18 F-choline, ranked as the most favorable with the highest value of AUC (AUC =0.94; 95% CI: 0.92–0.96), whereas 18 F-FDG was the least favorable (AUC =0.73; 95% CI: 0.69–0.77) for PCa detection (2). On the other hand, a recent review suggests that, 18 F-FDG might be helpful for restaging purposes in patients with advanced PCa metastatic disease.…”
Section: F-fluorodeoxyglucose (18f-fdg)mentioning
confidence: 98%
“…For patients with organ-confined PCa that is considered intermediate or high risk, primary curative approaches, including radical prostatectomy (RP) or radiation therapy (RT), are advised provided that there is no evidence of metastatic disease. On the other hand, when the disease is metastatic, systemic therapies are more suitable (2). …”
Section: Introductionmentioning
confidence: 99%
“…Radiation exposure 29 Cirrhosis and steatosis (induced by chemotherapy); imaging of cirrhotic or steatotic liver can be improved by using contrast agent 27,28 . Lack of anatomical orientation 23 Sensitivity, specificity of system Increases with field strength 19,25,55 Specificity > 90%, but sensitivity only 60% 20…”
Section: Iterativementioning
confidence: 99%
“…Lack of sensitivity owing to very low light levels 33 . Specificity dependent on tracer used 55 Increase in imaging distance degrades sensitivity and spatial resolution 34,37 . Sensitivity and specificity dependent on system and tracer 55 FOV, field of view; SLN, sentinel lymph node; SPECT, single-photon emission CT.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…18 F] fluoro-D-glucose, or 18 F-FDG; however, these tracers are limited by sensitivity, specificity, metabolism and excretion methods [17][18][19]. Thus, the purpose of this review is to highlight the advantages and limitations of current novel PET tracers in the detection of biochemical recurrent and metastatic PCa.…”
mentioning
confidence: 99%